Cloud-supported preservation of digital papers: A solution for special collections? - Weisbrod, Dirk (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Computers and other digital communication media have replaced paper and pencil from the writer’s desk. This development has confronted special collections with a problem, as digital papers are difficult to process using established digital preservation strategies, because of their individual and unique nature. According to the proposal suggested in this paper, the creators should instead be involved in the preservation process, and special collections should integrate pre-custodial forms of curation within their range of tasks. The article outlines the use of a cloud architecture as a suitable instrument for accomplishing this task. The benefits and the prospects for such a collection cloud are exposed and discussed.